Dietary Supplementation of the Antioxidant Curcumin Halts Systemic LPS-Induced Neuroinflammation-Associated Neurodegeneration and Memory/Synaptic Impairment via the JNK/NF-κB/Akt Signaling Pathway in Adult Rats. (7th November 2019) - Khan, Muhammad Sohail; Muhammad, Tahir; Ikram, Muhammad; Kim, Myeong Ok
Abstract : Curcumin is a natural polyphenolic compound widely known to have antioxidant, anti-inflammatory, and antiapoptotic properties. In the present study, we explored the neuroprotective effect of curcumin against lipopolysaccharide- (LPS-) induced reactive oxygen species- (ROS-) mediated neuroinflammation, neurodegeneration, and memory deficits in the adult rat hippocampus via regulation of the JNK/NF- κ B/Akt signaling pathway. Adult rats were treated intraperitoneally with LPS at a dose of 250  μ g/kg for 7 days and curcumin at a dose of 300 mg/kg for 14 days. After 14 days, the rats were sacrificed, and western blotting and ROS and lipid peroxidation assays were performed. For immunohistochemistry and confocal microscopy, the rats were perfused transcardially with 4% paraformaldehyde. In order to verify the JNK-dependent neuroprotective effect of curcumin and to confirm the in vivo results, HT-22 neuronal and BV2 microglial cells were exposed to LPS at a dose of 1  μ g/ml, curcumin 100  μ g/ml, and SP600125 (a specific JNK inhibitor) 20  μ M. Our immunohistochemical, immunofluorescence, and biochemical results revealed that curcumin inhibited LPS-induced oxidative stress by reducing malondialdehyde and 2, 7-dichlorofluorescein levels and ameliorating neuroinflammation and neuronal cell death via regulation of the JNK/NF- κ B/Akt signaling pathway both in vivo (adult rat hippocampus) and in vitro (HT-22/BV2 cell lines). Moreover, curcumin markedly improved LPS-induced memory impairment in the Morris water maze and Y-maze tasks. Taken together, our results suggest that curcumin may be a potential preventive and therapeutic candidate for LPS-induced ROS-mediated neurotoxicity and memory deficits in an adult rat model.